2018
DOI: 10.1152/ajpheart.00588.2017
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related increase in store-operated Ca2+ influx in human ventricular fibroblasts

Abstract: Senescence-related fibrosis contributes to cardiac dysfunction. Profibrotic processes are Ca dependent. The effect of aging on the Ca mobilization processes of human ventricular fibroblasts (hVFs) is unclear. Therefore, we tested whether aging altered intracellular Ca release and store-operated Ca entry (SOCE). Disease-free hVFs from 2- to 63-yr-old trauma victims were assessed for cytosolic Ca dynamics with fluo 3/confocal imaging. Angiotensin II or thapsigargin was used to release endoplasmic reticulum Ca in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Ca 2+ influx, and the expression of Orai1 but not STIM1, have been shown to be much larger in ventricular fibroblasts derived from failing hearts compared to those of non-failing hearts [68]. In aged ventricular fibroblasts, while store-operated Ca 2+ release and entry were shown to increase, the expressions of Orai1 and STIM1 remained unchanged [67]. These results suggest that Orai/STIM channels play a role in fibroblast Ca 2+ signaling, and may therefore contribute to cardiac remodeling under pathological conditions.…”
Section: Ca 2+ Entry Through Crac (Orai/stim) Channels In Cardiac Fibmentioning
confidence: 95%
See 1 more Smart Citation
“…Ca 2+ influx, and the expression of Orai1 but not STIM1, have been shown to be much larger in ventricular fibroblasts derived from failing hearts compared to those of non-failing hearts [68]. In aged ventricular fibroblasts, while store-operated Ca 2+ release and entry were shown to increase, the expressions of Orai1 and STIM1 remained unchanged [67]. These results suggest that Orai/STIM channels play a role in fibroblast Ca 2+ signaling, and may therefore contribute to cardiac remodeling under pathological conditions.…”
Section: Ca 2+ Entry Through Crac (Orai/stim) Channels In Cardiac Fibmentioning
confidence: 95%
“…In fibroblasts, although the Orai and STIM subunits have been detected by qPCR or RT-PCR in mouse and human cardiac fibroblasts [37,46], CRAC currents have not been recorded by patch-clamp [37]. Recently, the functional Orai1/STIM1 channels have been demonstrated by Ca 2+ imaging measurements in human ventricular fibroblasts [67,68,125]. Ca 2+ influx, and the expression of Orai1 but not STIM1, have been shown to be much larger in ventricular fibroblasts derived from failing hearts compared to those of non-failing hearts [68].…”
Section: Ca 2+ Entry Through Crac (Orai/stim) Channels In Cardiac Fibmentioning
confidence: 99%
“…This study suggests that STIM1/Orai1 may regulate cardiac fibroblast activity and activation. It has been shown that SOCE may increase in aged human cardiac fibroblasts which was associated with a reduction in the expression of pro-fibrotic sprouty homologue 1 (Spry1) possibly contributing to senescence-mediated fibrosis in the heart; however, in these studies expression levels of STIM/Orai were not changed ( Mohis et al, 2018 ) so the catalyst driving the increase in SOCE in this study remains unclear. Moving forward, it will be important better understand the different functions and roles of STIM and Orai isoforms in the various cell types of the heart and whether these STIM/Orai isoforms contribute to crosstalk between these cell types during physiological and pathophysiological instances.…”
Section: Physiological and Pathophysiological Roles Of Stim/orai In T...mentioning
confidence: 63%
“…87 Some studies have suggested that age-related fibrosis may be due to decreased matrix degradation rather than increased collagen synthesis. 88,89 Macrophages secrete stromal cell proteins and are directly involved in ECM remodelling by producing MMPs and their inhibitors.…”
Section: With Ageing Turnover Of Crm Composition Contributes To Augmmentioning
confidence: 99%